1991
DOI: 10.1203/00006450-199103000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Content and Type II Cell Development in Fetal Guinea Pig Lungs during Prenatal Starvation

Abstract: ABSTRACT. Prenatal caloric restriction in guinea pigs causes intrauterine growth retardation and reduced neonatal viability and surfactant phosopholipid (PL). We report here fetal surfactant levels in this model, and correlate total lung PL with ultrastructural maturation of surfactant type I1 cells and lamellar bodies (LB). Pregnant guinea pigs were fed ad libitum throughout their 68-d gestation (control), or fed 50% rations from d 45 until term (starved). Fetal lungs were examined at d 55, 60, and 65 for PL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…Total saturated phosphatidylcholine contents were lower in IUGR rats' lungs and the value reached statistical significance on postnatal d 1 only. These results are in agreement with the findings of Lechner et al (11,21), who found that prenatal starvation reduces total lung saturated phospholipids in fetal and term guinea pigs at birth. Ryan et al (25) administered LDL intravenously over 3 h to pregnant rats, and found that saturated phosphatidylcholine content is increased in fetal alveolar pretype II cells.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Total saturated phosphatidylcholine contents were lower in IUGR rats' lungs and the value reached statistical significance on postnatal d 1 only. These results are in agreement with the findings of Lechner et al (11,21), who found that prenatal starvation reduces total lung saturated phospholipids in fetal and term guinea pigs at birth. Ryan et al (25) administered LDL intravenously over 3 h to pregnant rats, and found that saturated phosphatidylcholine content is increased in fetal alveolar pretype II cells.…”
supporting
confidence: 83%
“…Maternal undernutrition during late gestation is associated with poor maternal weight gain and reduced fetal body weight in rats (13,21). IUGR caused by placental insufficiency in sheep reveals similar findings (22,23).…”
supporting
confidence: 65%
“…Although the molecular mechanisms underlying this respiratory compromise are not well established, general cellular and molecular effects of IUGR on the developing lung have been described. 415 These include an overall reduction in lung weight, DNA, and protein content, 46 reduced surfactant content and activity, 79 impaired maturation of the alveolar type II (ATII) cell, 10 decreased alveolar formation, 1113,15 reduced alveolar surface area for gas exchange, 11,14 an immature and thicker air-blood barrier, and a thicker alveolar wall. 10,14 …”
Section: Introductionmentioning
confidence: 99%
“…The infant of the poorly controlled diabetic mother has a higher incidence of respiratory distress syndrome [ 5,11] , and high insulin and glucose levels have both been found to inhibit fetal lung maturation in various experimental systems [5][6][7][8][9][10] . Maternal starvation also has been reported to result in decreased pulmonary surfactant content in fetal guinea pigs [ 26] .…”
Section: Discussionmentioning
confidence: 99%